Variation of the clinical spectrum and genotype-phenotype associations in Coenzyme Q10 deficiency associated glomerulopathy - Drovandi, Stefania; Lipska-Ziętkiewicz, Beata S.; Ozaltin, Fatih; Emma, Francesco; Gulhan, Bora; Boyer, Olivia; Trautmann, Agnes; Ziętkiewicz, Szymon; Xu, Hong; Shen, Qian; Rao, Jia; Riedhammer, Korbinian M.; et al. (Kidney international, 2022)
Primary Coenzyme Q10 deficiency is a rare mitochondriopathy with a wide spectrum of organ involvement, including steroid-resistant nephrotic syndrome mainly associated with disease-causing variants in the genes COQ2, COQ6 or COQ8B. We performed a systematic literature review, PodoNet, mitoNET, and CCGKDD registries queries and an online survey, collecting comprehensive clinical and genetic data of 251 patients spanning 173 published (47 updated) and 78 new cases. Kidney disease was first diagnosed at median age 1.0, 1.2 and 9.8 years in individuals with disease-causing variants in COQ2, COQ6 and COQ8B, respectively. Isolated kidney involvement at diagnosis occurred in 34% of COQ2, 10.8% of COQ6 and 70.7% of COQ8B variant individuals. Classic infantile multiorgan involvement comprised 22% of the COQ2 variant cohort while 47% of them developed neurological symptoms at median age 2.7 years. The association of steroid-resistant nephrotic syndrome and sensorineural hearing loss was confirmed as the distinctive phenotype of COQ6 variants, with hearing impairment manifesting at average age three years. None of the patients with COQ8B variants, but 50% of patients with COQ2 and COQ6 variants progressed to kidney failure by age five. At adult age, kidney survival was equally poor (20-25%) across all disorders. A number of sequence variants, including putative local founder mutations, had divergent clinical presentations, in terms of onset age, kidney and non-kidney manifestations and kidney survival. Milder kidney phenotype was present in those with biallelic truncating variants within the COQ8B variant cohort. Thus, significant intra- and inter-familial phenotype variability was observed, suggesting both genetic and non-genetic modifiers of disease severity.